The right to traditional, complementary, and alternative health care - Maria Stuttaford; Sahar Al Makhamreh; Fons Coomans; John Harrington; Chuma Himonga; Gillian Lewando Hundt (Taylor & Francis Group, 2014)
Background: State parties to human rights conventions and declarations are often faced with the seemingly contradictory problem of having an obligation to protect people from harmful practices while also having an obligation to enable access to culturally appropriate effective healing. As people increasingly migrate across the globe, previous distinctions between 'traditional' and 'complementary and alternative medicine' practices are being transcended. There are connections across transnational healing pathways that link local, national, and global movements of people and knowledge. Objective: This paper contributes to the development of the concept and practice of the right to health in all its forms, exploring the right to traditional, complementary, and alternative health (R2TCAH) across different contexts. Design: The paper draws on four settings - England, South Africa, Kenya, and Jordan - and is based on key informant interviews and a literature review undertaken in 2010, and updated in 2013. The paper begins by reviewing the international legal context for the right to health. It then considers legal and professional regulations from the global north and south. Results: Additional research is needed to establish the legal basis, compare regulatory frameworks, and explore patient and provider perspectives of regulation. This leads to being able to make recommendations on how to balance protection from harm and the obligation to ensure culturally appropriate services. Such an exploration must also challenge Western theories of human rights. Key concepts, such as individual harm, consent, and respect of the autonomy of the individual already established and recognised in international health law, could be adopted in the development of a template for future comparative research. Conclusions: Exploration of the normative content of the right to health in all its forms will contribute to supporting traditional, complementary, and alternative health service users and providers in terms of access to information, non-discrimination, clarification of state obligations, and accountability.